Ælius Aristide et Xénophon - RUBULOTTA, GABRIELLA (Brepols, 2025)
Several ancient literary sources show that Xenophon was regarded during the Imperial period as a preeminent model. This study looks at how Xenophon was received in the speeches of Ælius Aristides – an angle that has not been explored until now. The speeches examined include the <span class=